Problemas éticos en el desempeño profesional del médico colegiado de la libertad 2011 - Fernández Rodríguez, Lissett Jeanette (2013)
We determined the ethical problems, ethics experience and sociodemographic registered physicians of La Libertad. The study was descriptive. We surveyed 300 registered doctors using the ethical experience scale developed by Hurst and Col. The scale score ranges from 0 to 36. Then we asked for comments on the scale and note finally sex, age, home university, graduation year, employment status and professional performance. Permission from presidents of medical corps in the major hospitals in our region and the President of the Medical Association were requested for the survey application. Participation was voluntary and anonymous. Of the total participants (300), 31.6% are between 51 and 60 years, 76.9% male, 24.5% are between 21 to 30 years of service, 47.6% are appointed. 74% studied undergraduate at the National University of Trujillo. 53% are registered specialists. The 26.5% of registered doctors often refer ethical difficulties presented. The 35.8% usually showed disagree with the patient for religious or cultural reasons, 9.7% usually presented limited diagnostic and therapeutic resources and 8% patients often unable or unsafe treatment decisions are made. The average score of the scale was 13.38. The 51.3% of physician’s volunteers did not help address ethical problems. The ethical problem in the performance of professional medical practitioner of La Libertad is the disagreement with the patient for religious reasons.